Modified Supportive Simple Limbal Epithelial Transplantation (M-SLET): A surgical technique modified for limbal stem cell deficiency - Sameer G Datar; Gayatri N Godse (Indian Journal of Ophthalmology, 2022)
This study aimed to develop and modify the surgical technique of simple limbal epithelial transplantation in patients with limbal stem cell deficiency to provide support to epithelial explants during the post-operative period. This is a case series of five eyes of five patients who underwent modified supportive simple limbal epithelial transplantation (M-SLET) surgery. The health and stability of the ocular surface were assessed based on clinical slit lamp examination; they were the main outcome measures. All patients had a stable ocular surface and healed epithelium during all the follow-up visits. The M-SLET technique provides additional support to limbal epithelial explants, adhering to the cornea, thus creating a stable epithelial surface. This is particularly important when there is a risk of explants being dislodged by eye rubbing.